Literature Review: Foot Exercise Prevents the Risk of Neuropathy on Diabetes Mellitus Patient: Foot Exercise Prevents the Risk of Neuropathy on Type 2 Diabetes Mellitus Patient - Ryan Hidayat; Chita Widia (STIKep PPNI Jawa Barat, 2021)
Aims : Diabetes mellitus is a disease in which the body cannot automatically control glucose in its blood, a complication that often occurs in the lower limbs called diabetic feet. This study aims to determine the risk of neuropathy in type 2 diabetes mellitus sufferers who perform diabetic foot exercises. Design :The research design is the Literature Review type of Narrative Review. Methods :The literature search in this literature review uses two databases with high and medium quality criteria, namely Scopus, and Google Scholar, using keywords technique in English which arranged into one search sentence are